STUDENTS' PERCEPTION OF USING PAPERPAL AI AS AN AUTOMATED WRITING EVALUATION (AWE) TOOL ON WRITING GRAMMATICAL FEEDBACK - Nabila Yun Afifah; Utami Dewi (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
This study aims to explore university students’ perceptions of using Paperpal AI as an Automated Writing Evaluation (AWE) tool in providing grammatical feedback during the academic writing process. Grounded in the Technology Acceptance Model and Self- Regulated Learning Theory, this research addresses the gap in understanding how students critically engage with AI-driven feedback in English as a Foreign Language (EFL) contexts. A qualitative case study design was employed, involving 30 EFL university students majoring in English Education who had prior experience using Paperpal AI. Data were gathered through questionnaires and in-depth interviews. Questionnaire responses were analyzed descriptively using percentage analysis, while interview data were examined through Thematic Content Analysis (TCA). Findings revealed that students perceived Paperpal AI as beneficial for improving grammatical accuracy, sentence clarity, and editing efficiency. They appreciated the tool’s user-friendly interface and real-time feedback, particularly for grammar and transitions. However, concerns were raised regarding the general nature of suggestions, occasional contextual inaccuracy, and limited support for creativity. These insights suggest that while Paperpal AI enhances surface-level writing skills, it should be complemented with human feedback and critical reflection to support deeper writing development in academic settings.